Effect of scrubbing medium's particle size on scrubbing flotation performance and mineralogical characteristics of microcrystalline graphite. (15th March 2021) - Wang, Xuexia; Bu, Xiangning; Ni, Chao; Zhou, Shaoqi; Yang, Xiaolin; Zhang, Jing; Alheshibri, Muidh; Peng, Yaoli; Xie, Guangyuan
Graphical abstract: Highlights: Microcrystalline graphite was enriched efficiently under scrubbing flotation. Response surface methodology was used for the optimization of scrubbing flotation. The most significant parameter of scrubbing flotation was scrubbing medium size. Effect of scrubbing medium size on mineralogical characteristics was evaluated. Abstract: Scrubbing is a suitable method for cleaning fine slime on the surface of microcrystalline graphite, improving its flotation performance. However, little attention has been paid to the effect of the scrubbing medium's particle size on enrichment efficiency of scrubbing flotation of microcrystalline graphite. In this work, scrubbing parameters (i.e., scrubbing medium's particle size, stirring speed, and solid concentration) were optimized via response surface methodology using Box-Behnken design to yield the maximum enrichment efficiency of graphite ore. The scrubbing medium's particle size was found to be the most important influencing factor. The optimal conditions for scrubbing process were obtained and tested to confirm the results predicted by the Design-Expert software. The enrichment efficiency of graphite treated with scrubbing media of different sizes was compared under optimal stirring speed and solid concentration conditions. The effect of the scrubbing medium's particle size on the scrubbing flotation of graphite was investigated by a comparison of the graphite particle size distribution before and after scrubbing, and field emission scanning electron microscopic examination of raw ore and flotation concentrates.